605. Factors Underlying Antifungal Price Trends in the United States. (31st December 2020) - Thomas, Christine; Shae, Whitney; Koestler, Devin; DeFor, Terese; Bahr, Nathan; Alpern, Jonathan
Abstract: Background: Antifungal drugs are used to treat conditions ranging from topical dermatologic disease to life-threatening systemic infections. Given their widespread use, understanding factors that affect antifungal pricing will help clinical and policy-related decisions. The purpose of this study was to identify factors associated with price trends among antifungal drugs. Methods: Antifungal drug products available in the United States were identified using the Food and Drug Administration (FDA) Orange Book database. Multiple characteristics related to how a drug may be priced were identified using a variety of sources, including the number of FDA indications (IBM Micromedex), quantity of professional guideline recommendations and use as prophylaxis (Infectious Diseases Society of America guidelines for treatment of fungal infections), and route of administration. Wholesale acquisition cost per unit was identified for each drug from the first date listed through 2019 using the Medi-Span and First Databank databases. Statistical analysis was performed using R (version 3.6.3). Price trajectories over time observed on 138 antifungal drugs were clustered into three groups by the shape of their trajectory using the R package KmlShape (Genolini 2016). Clusters were characterized by stable prices, moderate price increases, and extreme price increases over time. Relationships between cluster membership and drug characteristics were assessed using Fisher's Exact Test and Likelihood Ratio Tests. All tests were conducted at the 5% level of significance. Results: The majority (n=116) of antifungal drugs were characterized by moderate price increase and an additional n=6 exhibited extreme price increases over time. Few (n=16) were stable. Associations were identified between drug characteristics and extreme price increase cluster membership. These included a fewer number of FDA indications (p=0.0028) and atypical route of administration (p=0.0025). No association was identified between cluster membership and quantity of guideline recommendations, or use as prophylaxis. Conclusion: Nearly 90% of antifungal drugs exhibited at least moderate price increases over time. Extreme price increases were associated with a fewer number of FDA indications and atypical route of administration. Disclosures: All Authors : No reported disclosures